Pre-harvest aminoethoxy vinylglycine (AVG) spray maintains fruit quality of apples (Malus cominnus L. cv. Red Chief) during cold storage - Kucuker, Emine; Aglar, Erdal (Journal of Postharvest Technology, 2024)
In the study, the effect of AVG application at different concentrations on the post-harvest fruit quality of apple cultivar (Malus cominnus L. cv.  Red Chief ) was investigated. The study consisted of four applications, 75, 150 and 225 mg/ L-1 AVG and control. AVG was applied 4 weeks  before anticipated harvest. The effect of AVG application on fruit size was inconsistent. 225 mg L-1 dose application increased fruit size while  the smaller fruit were harvested on the tress applied 75 mg L-1 AVG. It was determined that the weight losses during storage decreased with  AVG application. The more firmness fruit were harvested with 125 mg L-1AVG application while there was no significant difference in terms of  fruit firmness between other applications. The fruit firmness decreased in proportion to the cold storage period while the highest loss of fruit  firmness was recorded with the control application. In the study, fruit with higher acidity but lower Solible Solids Content (SSC) ratio were  harvested with AVG application. However, the effect of AVG concentration on titratable acidity and SSC ratio of the fruit was not significant. Depending on the cold storage period, the SSC ratio in the fruit increased while the titratable acidity ratio decreased. There was no difference  between the applications in the decrease in the titratable acidity ratio during cold storage. However, it was determined that the ratio of SSC in  AVG-applied fruit was lower than the control, but the application dose was not effective.
Keywords: Malus cominnus L; , Weight loss; acidity; fruit size; fruit firmness